FDTD Complex Terrain Modeling Method Based on Papery Contour Map - Meng Chen; Bing Wei; Xinbo He (International Journal of Antennas and Propagation, 2023)
This study aims to develop a finite difference time-domain (FDTD) modeling method for complex terrain using a paper contour map. First, the image preprocessing technology is employed to segment, denoise, and number the drawing area to arrive at independent figures and curve matrices. Subsequently, the support vector machine (SVM) classifier is implemented to identify the number and obtain the elevation value pertinent to the curve in the figure. Finally, the scattered points in the curve matrix are meshed by the Delaunay triangulation algorithm, and a three-dimensional triangular mesh model is established according to the recognition results. The FDTD calculation model is established by the method of intersection of Yee cell grid lines and triangle projection. The simulation results reveal that the recognition rate of the SVM classification model in this study is close to 100% for printed numerals. This approach is capable of quickly and accurately establishing the FDTD-based calculation model for complex terrain on the basis of the paper contour map.